Impact of a volume challenge on haemodynamics and prognosis in patients with severe aortic stenosis. (12th November 2020) - Maeder, Micha T.; Weber, Lukas; Weilenmann, Daniel; Haager, Philipp K.; Joerg, Lucas; Rohner, Franziska; Ammann, Peter; Chronis, Joannis; Rigger, Johannes; Rickli, Hans
Abstract: Aims: A volume challenge can unmask pulmonary hypertension (PH) and its mechanism. We evaluated the impact of a volume challenge on mean pulmonary artery pressure (mPAP) and mean pulmonary artery wedge pressure (mPAWP) and its prognostic implications in patients with severe aortic stenosis (AS) undergoing aortic valve replacement (AVR). Methods and results: In 285 patients with severe AS (indexed aortic valve area 0.41 ± 0.13 cm 2 /m 2 ), mPAP and mPAWP were measured before and after administration of 150 ± 58 mL of low‐osmolal or iso‐osmolal contrast. Following contrast, mPAP and mPAWP rose from 25 ± 10 and 16 ± 8 mmHg by 5 ± 4 and 4 ± 4 mmHg to 30 ± 11 and 20 ± 8 mmHg. There were 112 (39%) patients with pre‐contrast PH and 70 (40% of those without pre‐contrast PH) patients with post‐contrast PH only. Post‐contrast PH patients were intermediate between pre‐contrast PH and no PH in terms of AS severity, cardiac dysfunction, and haemodynamics. After a median follow‐up of 43 months post‐AVR, pre‐contrast PH patients had numerically the highest mortality driven by those with pre‐contrast combined pre‐capillary and post‐capillary PH ( n = 35), while post‐contrast changes in mPAP and mPAWP were not related to mortality. Patients with any post‐contrast mPAWP > 18 mmHg had significantly higher mortality than those with post‐contrast mPAWP ≤ 18 mmHg, Conclusions: In severe AS, a contrast challenge leads to post‐contrast PH in 40% of patients without pre‐contrast PH. However, post‐contrast haemodynamic changes do not adversely affect outcomes in patients undergoing AVR. Post‐contrast PH represents an intermediate stage of 'cardiac damage', which may be attenuated or reversible after AVR.